Biomechanical basis of human movement - Hamill, Joseph PhD; Knutzen, Kathleen M. PhD; Derrick, Timothy R. PhD
Master the full continuum of human movement potential with this rigorous yet approachable introduction to biomechanics. Focusing on the quantitative nature of biomechanics, Biomechanical Basis of Movement, fifth edition applies laws of motion and mechanics to in-depth analysis of specific movements, integrating current literature, meaningful numerical examples, relevant applications, hands-on exercises, and functional anatomy, physics, calculus, and physiology for a confident, comprehensive understanding of human movement.